Predatory journals: What can we do to protect their prey? - Christine Laine; Dianne Babski; Vivienne C Bachelet; Till W Bärnighausen; Christopher Baethge; Kirsten Bibbins-Domingo; Frank Frizelle; Laragh Gollogly; Sabine Kleinert; Elizabeth Loder; João Monteiro; Eric J Rubin; et al. (PLoS Medicine)
In this Editorial, representatives of the International Committee of Medical Editors discuss the need for multi-stakeholder involvement to recognize and counter the actions of predatory journals.